(untitled) (Canadian Journal of Native Studies, 2026)
The COVID-19 pandemic requires specific treaty-based strategies to address the unique position of First Nations communities across Canada within treaty territories. A treaty-based approach is necessary to recognize certain provisions set out in the Numbered Treaties in Canada. These provisions include the Famine and Pestilence Clause and Medicine Chest Clause, both clauses were agreed to during the Treaty #6 signing in 1876. In the Famine and Pestilence Clause the Crown agreed to provide assistance to the “Indian” Peoples in the event of any calamity that came upon them, such as locust raids, storms, starvation, or disease. The Medicine Chest Clause implements the means to provide the medical aid to go along with the Famine and Pestilence Clause. The Government of Canada has a legal obligation to immediately invoke the Famine and Pestilence Clause together with the Medicine Chest Clause in a strategy to address the spread of the COVID-19 pandemic.